Pengembangan Buku Panduan Konseling Kelompok dengan Teknik Behavior Contract untuk Meningkatkan Tanggung Jawab Akademik Siswa SMK - Lutfi Fauzan; Dede Ayu Anggraeni; Ella Faridati Zen; Dede Ayu Anggraeni; Ella Faridati Zen (Universitas Negeri Malang, 2021)
Abstract: This research is a research and development which aims to produce a group counseling manual with the behavior contract technique to increase the academic responsibility of students in vocational schools that are theoretically and practically acceptable. This research procedure adapted Borg and Gall's development model, namely knowing the potentials and problems found, collecting data and information, designing product guides, testing products by experts, and revising the final product. The results of the product trials indicated that the assessment of media experts and potential users stated that the product was